Reversal of subjective temporal order due to arm crossing - Yamamoto, Shinya; Kitazawa, Shigeru (Nature neuroscience, 2001)
How does the brain order successive events? Here we studied whether temporal order of two stimuli delivered in rapid succession, one to each hand, is determined before or after the stimuli are localized in space. When their arms were crossed, subjects could accurately report the temporal order, even when the interval between stimuli was as short as 70 ms. In most trials, subjects could also judge temporal order when their arms were crossed, but only if given adequate time (>1 s). At moderately short intervals (<300 ms), crossing the arms caused misreporting (that is, inverting) of the temporal order. Thus, at these intervals, the determining factor of temporal order was the spatial location of the hands. We suggest that it is not until the spatial locations of the hands are taken into account that the cutaneous signals from the respective hands are ordered in time.